The Comparison of Trust Towards Political Institutions Between Caucasian Countries and Turkey - Cetin, Dilek; Cirpici, Yasemin Asu (BC GRUP INC, 2017)
Economies not only have higher growth rates but also have less effected from the economic crisis in an environment with trust (Tonkiss. 1999). To ensure the trust in the economy is the prerequisite for both the political and economic stability. The main of this study is to compare the trust towards political institutions between Caucasian Countries (Azerbaijan, Georgia and Armenia) and Turkey. The parliament, the armed forces, the police and the press are examples of political institutions. To test the hypothesis, European Values Survey (EVS) is utilized. The survey is conducted in 2008. The number of observations for Azerbaijan, Georgia, Armenia and Turkey is 1505, 1500, 1500 and 2384. respectively. The ANOVA method is used to test the hypothesis of whether there are differences across countries according to trust towards political institutions or not.
Keywords: Trust; Turkey; Caucasus; ANOVA; Business & Economics; Social Issues